Praktik Akuntansi dalam Penetapan Nilai Mahar (Boka) Pada Pernikahan Adat Buton di Kota Baubau: Accounting Practices in Determining The Value of Dowry (Boka) In Buton Custom Weddings In Baubau City - febby rachmadani; Wiliana, Rahayu; Pagalung, Gagaring; Ayu Damayanti, Ratna (Universitas Bojonegoro, 2024)
This study aims to reveal culture accounting practices in the process of determining the dowry value (boka) in traditional marriage of the Buton People in Baubau City. This research is a qualitative descriptive. Data collection was carried out through observation, interviews and documentation. The result showed that the accounting practice in determining the nominal value of the dowry (boka) was carried out in three stages, namely lukuti, pesoloi/pesolopi, and losa. The value of the dowry (boka) can be influenced by the level of the bride’s traditional social status. There is no bargaining process in the process of determining the dowry (tauraka). The process of determining the dowry (tauraka) is different from the process of setting accounting prices. Culture constructs reverse accounting with conventional accounting. Culture values are higher in values than money. Customs is above the transaction. Love underlies marriage so that the noble values of the Buton-Baubau Tribe are used in the entire process of determining the dowry (tauraka). 5 cultural values as well as money and gold as a means of paying the dowry (tauraka) of the Buton-Baubau Indigenous Tribe. The researcher found 5 meanings of the dowry value (boka) contained in the traditional wedding culture of the Buton-Baubau tribe, namely: respect, respect, readiness and responsibility, requests for permission and blessing. Prices are not always seen based on materials and numbers. Price has a different meaning from the point of view of the Buton-Baubau people.